Public Service Information System Analysis On The Sibisa Application Disdukcapil Medan In Improving Transparency And Government Accountability City Area Medan - Ashara Putri; Irawan; Fitri Yani Panggabean (Yayasan Multidimensi Kreatif, 2024)
This research aims to find out how the public service information system in the Medan Disdukcapil SIBISA application can increase the transparency and accountability of the Medan City regional government. This type of research is descriptive research with a qualitative approach. Data collection methods used include observation, interviews and documentation studies. The data obtained was analyzed descriptively. The research sample consisted of ASN employees of the Medan Disdukcapil with data collection techniques through interviews, document analysis, and observation, as well as data analysis techniques including data reduction, data presentation, and drawing conclusions. The research results show that the SIBISA application is effective in increasing transparency and accountability through easy access to information and document tracking, even though there are obstacles such as lack of training, socialization, system limitations that require physical documents, and less than optimal coordination. The strategic steps taken by the Medan City Dukcapil Department through CASCADING, LAKIP and LRA data show a commitment to improving the transparency and accountability performance of the Medan City regional government.